Integrated Marketing Communication in Building Brand Equity in the Social Media Era - Purwati, Ani; Ariyani, Nafiah (Ilomata International Journal of Social Science, 2025)
Social media provides a great opportunity for companies or brand owners and sellers to build and increase brand awareness, brand association, brand loyalty, perceived quality, and proprietary assets through Integrated Marketing Communication. This study adopts a qualitative approach with a literature review and content analysis to analyze the application of Integrated Marketing Communication on social media and its impact on brand equity elements. The results show that integrating integrated marketing communication on social media can build brand equity and increase brand awareness, brand association, loyalty, perceived quality, and proprietary assets. The Integrated Marketing Communication marketing mix elements also play a role by integrating various communication strategies to convey consistent and effective messages through advertising, sales promotion, public relations, direct marketing, personal selling, interactive marketing, word-of-mouth marketing, and events and experiences). Paid advertising, organic content, engagement, hashtags and collaborative campaigns, content marketing, and live streaming are other important elements to create a consistent brand experience and strengthen the relationship between brands and consumers. In conclusion, Integrated Marketing Communication on social media can build brand equity, which increases awareness, association, quality perception, and brand loyalty. Elements such as paid advertising, organic content, and influencer collaborations create a consistent experience that strengthens emotional connections with audiences while building sustainable brand equity and competitiveness in the market. These findings contribute to academics and practitioners in understanding effective digital marketing communication strategies in the digital era.